Coupling of Physiological and Proteomic Analysis to Understand the Ethylene- and Chilling-Induced Kiwifruit Ripening Syndrome - Minas, Ioannis S.; Tanou, Georgia; Karagiannis, Evangelos; Belghazi, Maya; Molassiotis, Athanassios (Frontiers in Plant Science, 2016)
Kiwifruit [Actinidia deliciosa (A. Chev.) C.F. Liang et A.R. Ferguson, cv. “Hayward”] is classified as climacteric fruit and the initiation of endogenous ethylene production following harvest is induced by exogenous ethylene or chilling exposure. To understand the biological basis of this “dilemma,” kiwifruit ripening responses were characterized at 20°C following treatments with exogenous ethylene (100 μL L−1, 20°C, 24 h) or/and chilling temperature (0°C, 10 days). All treatments elicited kiwifruit ripening and induced softening and endogenous ethylene biosynthesis, as determined by 1-aminocyclopropane-1-carboxylic acid (ACC) content and ACC synthase (ACS) and ACC oxidase (ACO) enzyme activities after 10 days of ripening at 20°C. Comparative proteomic analysis using two-dimensional gel electrophoresis (2DE-PAGE) and nanoscale liquid chromatography coupled to tandem mass spectrometry (nanoLC-MS/MS) revealed 81 kiwifruit proteins associated with ripening. Thirty-one kiwifruit proteins were identified as commonly regulated by the three treatments accompanied by dynamic changes of 10 proteins specific to exogenous ethylene, 2 to chilling treatment, and 12 to their combination. Ethylene and/or chilling-responsive proteins were mainly involved in disease/defense, energy, protein destination/storage, and cell structure/cell wall. Interactions between the identified proteins were demonstrated by bioinformatics analysis, allowing a more complete insight into biological pathways and molecular functions affected by ripening. The present approach provides a quantitative basis for understanding the ethylene- and chilling-induced kiwifruit ripening and climacteric fruit ripening in general.